THE EFFECT OF THE GOVERNMENT'S FREE NUTRITIOUS FOOD PROGRAM ON CHANGES IN LEARNING CONCENTRATION AND NUTRITIONAL STATUS IN STUDENTS OF SDN NO. 075062 DOLI-DOLI MANDREHE DISTRICT, WEST NIAS REGENCY - Ernawati Hondro; Ermi Girsang; Sri Lestari Ramadhani Nasution (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the effect of the Government’s Free Nutritious Food Program (MBG) on changes in learning concentration and nutritional status among students at SDN No. 075062 Doli-Doli, Mandrehe District, West Nias Regency. This research used a quantitative, quasi-experimental design with a pretest and posttest (no control group). The population consisted of 168 students, with a sample of 128 students selected using the Slovin formula and purposive sampling. Learning concentration was measured using a structured test, while nutritional status was assessed using Body Mass Index (BMI) based on anthropometric measurements. Data were analyzed using univariate methods and the Wilcoxon signed-rank test due to non-normal distributions. The results showed a significant increase in learning concentration (from pretest 30.19 to posttest 34.91; p < 0.001) and nutritional status (from pretest 15.33 to posttest 16.17; p < 0.001). These findings indicate that the MBG program significantly improves students' cognitive performance and nutritional status. The study concludes that school-based nutrition interventions are effective in supporting both health and educational outcomes, particularly in disadvantaged areas.